A novel design of in‐line static mixer for permanganate/bisulfite process: Numerical simulations and pilot‐scale testing. (26th May 2022) - Lei, Han; Guan, Xiaohong; Sun, Yuankui; Yan, Hexiang
Abstract: An increasing number of chemical technologies to wipe out contaminants within an incredibly short period of time have been developed recently, while their application was always hindered by the inefficient or improper mixing of reactants. To address this issue, the present work proposed a new static mixer named Tai‐Chi which consists of blade, fin, and spoiler elements. Tai‐Chi mixer can slice and divert the solutions inside and generate high shear flow to promote mixing process. Numerical simulations helped to determine the optimal operating conditions for Tai‐Chi mixer, including laying its components anterior to the injection nozzles and keeping the velocity rate ratio of main pipe to branch pipe within the range of 0.5 to 1. Numerical simulations further proved that Tai‐Chi mixer could strike a great balance between mixing performance (coefficient of variation [CoV] reaches 0.1 within 5 to 7 pipe diameters downstream) and head loss (nearly a half of other high shear static mixer in the market). Data of pilot‐scale testing by Tai‐Chi mixer confirm that 80% sulfamethoxazole could be eliminated in permanganate/bisulfite process within 8 pipe diameters, as well as showed the superiority of Tai‐Chi's mixing performance in early stage compared with other static mixers in the market. Practitioner Points: A Tai‐Chi static mixer with blade, fin, and spoiler elements is devised. The optimal condition of flow rate and installment of Tai‐Chi mixer is determined. Ultra‐fast mixing is achieved by Tai‐Chi (CoV < 0.1 within 5–7 pipe diameters). Pilot‐scale test verifies the mixing efficiency of Tai‐Chi mixer. Abstract : A new in‐line static mixer named Tai‐Chi mixer has been invented. CFD and 3D printing were both employed to verify that Tai‐Chi mixer could not only strike a great balance between mixing efficiency and head loss but also showed great advantage in the early mixing stage compared with other products on the market.